Procalcitonin as a Marker of Serious Bacterial Infections in Febrile Children Younger Than 3 Years Old. (February 2014) - Mahajan, Prashant; Grzybowski, Mary; Chen, Xinguang; Kannikeswaran, Nirupama; Stanley, Rachel; Singal, Bonita; Hoyle, John; Borgialli, Dominic; Duffy, Elizabeth; Kuppermann, Nathan; Alpern, Elizabeth
Abstract Objectives There is no perfectly sensitive or specific test for identifying young, febrile infants and children with occult serious bacterial infections (SBIs). Studies of procalcitonin (PCT), a 116‐amino‐acid precursor of the hormone calcitonin, have demonstrated its potential as an acute‐phase biomarker for SBI. The objective of this study was to compare performance of serum PCT with traditional screening tests for detecting SBIs in young febrile infants and children. Methods This was a prospective, multicenter study on a convenience sample from May 2004 to December 2005. The study was conducted in four emergency departments (EDs): one pediatric ED and three EDs with pediatric units, all with academic faculty on staff. A total of 226 febrile children 36 months old or younger who presented to the four participating EDs and were evaluated for SBI by blood, urine, and/or cerebral spinal fluid (CSF) cultures were included. Results The test characteristics (with 95% confidence intervals [CIs]) of the white blood cell (WBC) counts including neutrophil and band counts were compared with PCT for identifying SBI. Thirty children had SBIs (13.3%, 95% CI = 8.85 to 17.70). Four (13.3%) had bacteremia (including one with meningitis), 18 (60.0%) had urinary tract infections (UTIs), and eight (26.6%) had pneumonia. Children with SBIs had higher WBC counts (18.6 × 109 ± 8.6 × 109 cells/L vs. 11.5 × 109 ± 5.3 × 109 cells/L, p < 0.001), higher absolute neutrophil counts (ANCs; 10.6 × 109 ± 6.7 × 109 cells/L vs. 5.6 × 109 ± 3.8 × 109 cells/L, p = 0.009), higher absolute band counts (0.90 × 109 ± 1.1 × 109 cells/L vs. 0.35 × 109 ± 0.6 × 109 cells/L, p = 0.009), and higher PCT levels (2.9 ± 5.6 ng/mL vs. 0.4 ± 0.8 ng/mL, p = 0.021) than those without SBIs. In a multivariable logistic regression analysis, the absolute band count and PCT were the two screening tests independently associated with SBI, although the area under the receiver operating characteristic (ROC) curve for PCT was the largest (0.80, 95% CI = 0.71 to 0.89). Conclusions Procalcitonin is a more accurate biomarker than traditional screening tests for identifying young febrile infants and children with serious SBIs. Further study on a larger cohort of young febrile children is required to definitively determine the benefit of PCT over traditional laboratory screening tests for SBIs.